Mutational analysis of SMN gene in patients with spinal muscular atrophy and the correlation between mutation and the severity of clinical manifestations - Almagul Nagimtaeeva; Dina Zhanataeva; Bakytgul Kamalieva; Gulshara Abildinova (National Scientific Medical Center, 2017)
Objective: studying of mutations in the SMN1, SMN2 and NAIP genes in the diagnosis of spinal muscular atrophy and determining the correlation between the mutation and the severity of clinical manifestations. Methods: 82 children with suspicion of spinal muscular atrophy were examined. Genomic DNA was isolated from the whole blood of patients using the Wizard®Genomic DNA Purifcation kit (Promega). Further diagnostics was carried out using the MLPA method on a 96-capillary automatic analyzer 3730xl DNA Analyzer. The results were processed using the software Coﬀalyser DB.v.130. Results: A homozygous deletion of the exons 7-8 of the SMN1 gene was observed in all SMA patients of this study. At the same time, the deletion of the exon 7 of the SMN1 gene and an increase in the number of copies of SMN2, 1 (2%) and 2 (4%), respectively, were found among patients with type II and III type of SMA. In the analysis of deletions of exons 7-8 of the SMN1 gene, the SMN1 gene was completely deleted in 15 (29%), 2 (4%) and 1 (2%) SMA I, II and III patients. The study revealed that the NAIP gene was deleted in 8 patients (19.2%) with type I CMA and in two patients (4%) with SMA type II. Also, in a single patient with a type II SMA, deletions of the exon 8 of the SMN1 1 gene (2%) was found. Conclusion: the MLPA method allows not only to confrm the diagnosis of spinal amyotrophy, but also to specify the type of spinal amyotrophy depending on the detected changes in the SMN1, SMN2 and NAIP genes. The clinical diagnosis of SMA is mainly based on the identifcation of homozygous deletions of the 7th and 8th exons of the SMN1 gene. Deletion of the NAIP gene and an increase in the number of copies of SMN2 are considered to assess the clinical phenotype of CMA patients.